Preoperative Changes of Lung Nodule on Computed Tomography and Their Relationship With Pathological Outcomes - Zhou, Shihong; Cai, Deng; Chen, Chunji; Luo, Jizhuang; Wang, Rui (Frontiers in Surgery, 2022)
Background: Whether changes of resectable lung nodules on computed tomography could bring us helpful information relating to their pathological outcomes remained unclear. Materials and Methods: This retrospective study was carried out among 1185 cases of resectable lung nodules in Shanghai Chest Hospital from January 2015 to April 2017, which didn’t shrink or disappear after preoperative follow-up over three months. Their imaging features, changes and clinical characteristics were collected. Separate analysis was performed in nodules with or without growth in long-axis diameter after follow-up, searching significant changes relating to nodule malignancy and the median interval of follow-up for reference. Further study was performed similarly in malignant nodules for discrimination of malignant grading. Results: Most nodules were stable (n=885, 75%), while others grew (n=300, 25%). For predicting nodule malignancy, increase in density (>10 Hounsfield Units, median follow-up of 549 days) played an important role in growing group while it failed in stable group, and increase in size was less significant in growing group. For discrimination of malignant grading, increase in density (>70 Hounsfield Units, median follow-up of 366 days) showed its significancy in stable group, and so did increase in size in growing group (Maximum Diameter growth >3.3 millimeters, median follow-up of 549 days, or Average Diameter growth >3.1 millimeters, median follow-up of 625 days). Conclusions: There were significant changes of resectable lung nodules by follow-up on computed tomography, relating to their pathological outcomes. The predictive power of increase in density or size varied in different situation, while all referred to a long-time preoperative follow-up.